Collaborative Governancein the Management Of Slum Areas in Bekasi City - Hanung Hestiwati; Didi Turmudzi; Yaya Mulyana Abdul Aziz (Pasundan Social Science Development, 2022)
Bekasi City as part of Jabodetabek has 60 slum locations spread across 9 sub-districts (Kemen PUPR, 2014). The number of slum settlements increased in 2016 to 118 slum locations spread across 12 districts and 56 urban villages. In 2017 the slum settlements again increased to 122 locations. The slums in Bekasi have an area of ??443.73 hectares or 0.19 percent of the total area of ??Bekasi City. One strategy that can be used to manage slum areas in Bekasi City is to implement collaborative governance. which consists of the dimensions of the system context, drivers, and collaborative dynamics. The focus of this research is to emphasize collaborative governance processes in the management of slum areas in Bekasi City, and the results of collaboration from collaborative governance processes. The construction of thinking in this study is mapped into three parts, namely the grand theory (Organizational theory), middle range theory (Governance Theory) and applied theory (Collaborative Governance Theory). This study uses a qualitative approach, with a case study research strategy. The operational design of this study uses the An Integrative Framework for Collaboration Governance approach from Emerson et al (2011). It was revealed that processcollaborative governance in the management of slum areas in Bekasi City, the system context dimension is an environmental condition that overshadows the sustainability of collaborative governance. This system context creates opportunities and constraints that affect other parameters of collaborative governance. The results of this study also indicate that a minimum of a driving factor is needed to create a collaborative governance in the management of slum areas in Bekasi City. The more elements of the drivers involved, the greater the opportunities for the collaboration process to occur. The dynamics of collaboration is said to be good or not depending on three components, namely the mobilization of shared principles, shared motivation, and the capacity to take joint action.